Editando en común: Book Mutual Aid in Contemporary Radical Publishing Networks. - Rabasa, Magalí (Hispanic Review)
This article examines how notions of the collective anchored in both autonomous knowledge practices and communal approaches to intellectual property can be seen as throughlines that connect diverse experiments with radical publishing that have flourished and expanded over the past 25 years in Latin America. The analysis focuses on two cases based in Buenos Aires at different moments: an autonomous archive of independent presses called)el asunto(founded in the wake of the 2001 crisis, and an experimental novel, Magia y pérdida , by Anahí Ferreyra published in the context of the new feminist movement. Situating these two projects in a broader hemispheric movement of radical publishing, the article proposes the concept of book mutual aid as a way of thinking about the politicization of book production as an anticapitalist and feminist practice in the 21st century.